"The Peruvian Constitution and article 5 of the Military Government Statute of 1968" - Borea Odría, Alberto (1978)
In Peru, on October 3, 1968, there was a coup d'état. As a result, the Revolutionary Government of the Armed Forces was established and would be in power for twelve years. In this context, the military government announced that they would act in accordance with Article 5 of its own Statute which stated the following: "The Revolution Government shall act in accordance with the provisions of this Statute and those of the State Constitution, Laws and other provisions insofar as they are compatible with the objectives of the Revolutionary Government". Based on all this, the author is of the opinion that said government, although it justifies its action in arguments that are not so legalistic; even their actions can be included within the programmatic part of the Constitution. The latter refers to the first 83 articles where individual, social and national rights are covered. That is to say, this is the part in which it is indicated that the Government that is adopted must respect and guarantee the rights of individuals in the face of state intervention. In that sense, a constitutional analysis of the following reforms will be made: Agrarian Reform Law, Water Law, Industrial Community Law, Law of expropriation of the fishing industry, expropriation of newspapers and the Law of social property. In conclusion, this article analyzes the reforms introduced by the Military Government according to the Political Constitution. In that sense, the author presents the opinion that our Magna Carta has fulfilled a function of legitimization under Article 5 of the Statute. However, emphasis is placed on the fact that there have been conflicts between the Constitution and acts of government in the case of acts of repression.